A Comparative Study on Physical Function Test between Faller Group and Nonfaller Group among Community-Dwelling Elderly - Kyung Rim Shin, RN, EdD, FAAN; Younhee Kang, RN, MSN-ANP, PhD; Dukyoo Jung, RN, PhD; Miyoung Kim, RN, PhD; Eliza Lee, RN, PhD (Elsevier, 2012)
Purpose: This study aimed to identify the physical function test differences between the faller group and the nonfaller group in a sample of the community-dwelling elderly. Methods: This study used a nonexperimental two-group-comparative study design. The participants were 356 people aged 65 years and over living in an urban area. From May to December 2010, data were collected through personal interviews using questionnaires and measurements of muscle strength, physical endurance, flexibility, motor agility and dynamic balance, and static balance. The collected data were analyzed by descriptive statistics, Chi square analysis, and t test. Results: Upper muscle strength was significantly weaker in the faller group (p<.05). Lower muscle strength was significantly weaker in the faller group; both hip flexion (p=.004), knee extension (Right: p=.004; Left: p=.031), left ankle plantar flexion (p=.045), and left ankle inversion (p=.036). Tandem standing with eyes opened and closed was significantly shorter, indicating decreased static balance in the faller group. Conclusion: Nurses should make efforts to implement exercise programs focused on physical fitness enhancement for community-dwelling elderly adults for fall prevention.